Influence of weight ratio of conductive additive to binder in an electrode on the capacity of Li-ion battery. (23rd June 2022) - Lee, Jung-hoon; Kim, Cheol
Changes in the charge and discharge capacity of a lithium-ion battery are investigated by varying the percentage weight composition ratios of conductive additive to polymeric binder in an electrode of a lithium-ion battery. The cathode is made of active material (LiMn2 O4 ), binder (PVDF), and conductive additive (carbon black). To investigate the effect of inactive material composition on battery performance experimentally, the weight percentage of active material in the cathode is fixed at 85 wt% and five different ratios of PVDF/carbon black are assessed by varying conductive additive from 1.5 wt% to 13.5 wt% and binder from 13.5 wt% to 1.5 wt% while fabricating lithium-ion batteries. To study particles' cohesive behaviours between inactive materials in the electrode, various SEM images are taken and analysed for five different compositions of carbon black and PVDF. As a result, the improved battery performance is observed at the ratios of 7.5 wt%-10.5 wt% carbon black and 7.5 wt%-4.5 wt% PVDF.